Characterization on starches from non-cereal crops cultivated in tropical America: comparative analysis of staarch behaviour under different stress conditions - Dufour, D.L.; Hurtado Bermudez, Jhon Jairo; Wheatley, Christopher C. (International Center for Tropical Agriculture, 2000)
By studying the physical properties of native starches, new market opportunities can be identified for certain root and tuber crops, thus promoting renewed interest in their cultivation.